2014
DOI: 10.1371/journal.pone.0091947
|View full text |Cite
|
Sign up to set email alerts
|

Non-Thermal Atmospheric Pressure Plasma Preferentially Induces Apoptosis in p53-Mutated Cancer Cells by Activating ROS Stress-Response Pathways

Abstract: Non-thermal atmospheric pressure plasma (NTAPP) is an ionized gas at room temperature and has potential as a new apoptosis-promoting cancer therapy that acts by generating reactive oxygen species (ROS). However, it is imperative to determine its selectivity and standardize the components and composition of NTAPP. Here, we designed an NTAPP-generating apparatus combined with a He gas feeding system and demonstrated its high selectivity toward p53-mutated cancer cells. We first determined the proper conditions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
145
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 57 publications
4
145
2
1
Order By: Relevance
“…Ma et al demonstrated that the effectiveness of non-thermal plasma treatment was partially dependent on p53 expression [19]. The viability of cancer cells lacking p53 was significantly reduced by non-thermal plasma treatment while p53 + cells were less affected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ma et al demonstrated that the effectiveness of non-thermal plasma treatment was partially dependent on p53 expression [19]. The viability of cancer cells lacking p53 was significantly reduced by non-thermal plasma treatment while p53 + cells were less affected.…”
Section: Discussionmentioning
confidence: 99%
“…An important step to make this a reality is to determine the correct dose of CAP to significantly reduce tumor cell viability. It has been reported that various cell lines react differently to CAP treatment [17][18][19][20]. Yan et al studied the reactive species consumption speed of glioblastoma U87 and breast cancers MDA-MB-231 and MCF-7, and discovered that the cancer cells that could absorb or eliminate the effective species in the media faster (glioblastoma) were more resistant to plasma-activated media than both breast cancers [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, murine models of cutaneous carcinogenesis found that bypassing the loss of INPP5A with IP6 reduced tumour formation at the initiation phase of carcinogenesis. 9 In vitro studies of other cancers, such as breast, have…”
mentioning
confidence: 99%
“…3,4 Interestingly, the tumour-selectivity and apoptotic effect of CAP are especially high in p53-mutated cancer cells. 9 Dysregulation of the p53 pathway plays an important role in inducing clonal keratinocytic expansion in AK and SCC. 7 As human papilloma viruses are considered cocarcinogenic in AK and SCC development, 7 and infected keratinocytes frequently express HPV oncoproteins, virocide properties of CAP might work synergistically.…”
mentioning
confidence: 99%